Apolipoprotein M in patients with chronic kidney disease. (August 2018) - Sørensen, Ida MH.; Bertelsen, Marianne; Freese, Ellen; Lindhard, Kristine; Ullum, Henrik; Feldt-Rasmussen, Bo; Nielsen, Lars Bo; Christoffersen, Christina; Bro, Susanne
Abstract: Background and aims: Plasma apolipoprotein M (APOM) is bound to HDL-particles and has anti-atherogenic effects. The present study explored whether plasma APOM is reduced in patients with chronic kidney disease (CKD), and associated with cardiovascular disease (CVD). In addition, we tested the hypothesis that the excretion of APOM into the urine is increased in patients with kidney disease. Methods: Plasma samples were collected from a cohort of patients with CKD stages 1 to 5D (N = 409) and controls (N = 35). Urine was collected from 47 subjects. Plasma APOM was measured with sandwich ELISA and urine APOM with competitive ELISA. Results: Plasma APOM levels were reduced in patients with CKD stages 3-5D as compared to patients with CKD stages 1 + 2 and controls ( p  < 0.01). CKD patients with known CVD displayed even further reduction in plasma APOM levels than CKD patients without known CVD ( p  < 0.001). Fast-phase liquid chromatography showed that plasma APOM was primarily associated with HDL-cholesterol (HDL-C) across CKD stages. Accordingly, when plasma APOM values were corrected for HDL-C, a significant difference only persisted between patients with CKD stage 3 and stages 1 + 2 ( p  < 0.05), and the difference between CKD patients with and without known CVD disappeared. Urine APOM/creatinine ratio was not significantly increased in patients with kidney disease. Conclusions: The results show that the difference in plasma APOM levels observed between patients with mild and advanced CKD may mainly be due to differences in plasma HDL-C. Whether APOM plays a role in human uremic atherogenesis warrants further experimental studies.